2019
DOI: 10.1002/adom.201801666
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Cherenkov Radiation and Smith–Purcell Radiation by Artificial Structures

Abstract: A moving charged particle, such as an electron, can radiate light due to the interaction between its Coulomb field and surrounding matter. This phenomenon has spawned great interest in the fields of physics, electron microscopy, optics, biology, and materials science. Since the radiation generated by the charged particles strongly depends on the surrounding matter, artificially engineered materials with exotic electromagnetic and optic properties, including metamaterials and metasurfaces, provide an unpreceden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 120 publications
0
28
0
Order By: Relevance
“…Finally, more interesting physical systems, such as paritytime symmetry, [189][190][191] Smith-Purcell emission, [192][193][194][195] 2D materials [196][197][198] and topology, [199][200][201] could be introduced as a new DOF. For these research areas, metasurfaces provide an unprecedented opportunity to tailor their inner properties.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, more interesting physical systems, such as paritytime symmetry, [189][190][191] Smith-Purcell emission, [192][193][194][195] 2D materials [196][197][198] and topology, [199][200][201] could be introduced as a new DOF. For these research areas, metasurfaces provide an unprecedented opportunity to tailor their inner properties.…”
Section: Discussionmentioning
confidence: 99%
“…The useful range of electron kinetic energies runs the gamut from non-relativistic energies, as low as 50 eV in applications like coherent low-energy electron microscopy 5 10 , to ultra-relativistic energies, as high as several GeV in X-ray free electron laser facilities 11 , 12 . Broader applications of free electron sources include electron beam lithography 13 , 14 , atom-by-atom matter assembly 15 , nanoscale radiation sources 16 36 , and electron microscopy 37 47 .…”
Section: Introductionmentioning
confidence: 99%
“…The wide variety of structured materials provides powerful tools to control emission behaviors of free-electron radiation that leads to many significant findings [15][16][17][18][19][20][21][22][23]. Simply within the topic of Cherenkov radiation, the relevant studies have continuously demonstrated new phenomena include nondivergent [24], threshold-free [25] and reversed Cherenkov radiation [26].…”
Section: Introductionmentioning
confidence: 99%